Tax Revenue and Economic Development in Nigeria - Olaoye, Clement Olatunji; Ogundipe, Ayobolawole Adewale; Oluwadare, Oladimeji Emmanuel (Advances in Social Sciences Research Journal, 2019)
This study investigated the impact of taxation on economic development of Nigeria from 2003 to 2017.Vector Error Correction Model (VECM), Augmented Dickey-Fuller (ADF) unit root test, Autoregressive Distributed Lag (ARDL) bounds test, Jarque-Bera Normality Test and Eigenvalue stability condition were utilised in this study. The study revealed that companies’ income tax, petroleum profit and value added tax have a long run impact of -0.225(p-value=0.000),-0.0005 (p-value=0.699), and 0.211(p-value=0.000) respectively on the economic development of Nigeria.It was concluded that taxation has a significant long run relationship with Nigeria’s economic development. The study recommended that the government should not increase companies’ income tax rate because it is detrimental to the economic development of the country in the long run, instead the government should increase the value added tax because it has the potentiality to improve economic development of Nigeria. Also, the government should not concentrate effort on petroleum profit tax as it not significant on economic development of the country.